STANDAR KELAYAKAN BERITA ONLINE SEBAGAI SUMBER INFORMASI PEMBERITAAN MEDIA RADIO - Yulianda, Dewi; Suherdiana, Dadan; Fakhruroji, Moch (Annaba: Jurnal Ilmu Jurnalistik, 2022)
This thesis discusses the eligibility standards of online news as a source of information for media coverage and Radio Republik Indonesia in the city of Bandung. In a related discussion about how the standard of eligibility of an online news to be packaged into news broadcast on the radio. Therefore, in this thesis the author has a research focus, namely how important, factual, actual and interesting aspects in an online news source as news sources for Radio Republik Indonesia Bandung (RRI Bandung). The results of the research from the related title that the standard of eligibility for online news as a source of information for reporting on Radio Republik Indonesia media in the Bandung area (RRI Bandung) is seen from four aspects, namely important aspects, actual aspects, factual aspects and interesting aspects which are categorized as important owned by radio media such as RRI Bandung. because by fulfilling these four aspects the information broadcast is proven to be reliable so that the news conveyed is true.